PERAN MEDIA KOMUNIKASI SIMBOLIK SUKU MARIND MARGA GEBZE DALAM UPAYA PELESTARIAN BUDAYA - Ridmasari , Gloria; Sampoerno, Sampoerno; Krisnawati, Ester (Asosiasi Dosen Muda Indonesia, 2024)
Merauke is a city located at the eastern end of Indonesia and the native tribe of merauke is the marind. Each tribe has seven different clans and each has a symbol to identify: kaize, balagaize, gebze, mahuze, ndiken, basket-basik, samkakai. But the current writer focuses on the wrong side of a clan called the gebze clan that has a symbol or is commonly called the coconut totem. The coconut totem designated as a symbol of the gebze clan has a special meaning. The coconut raised asa symbol of the clan has reason that everyone especially the marind people should be strong, sturdy, growing like a coconut in which the coconut is promoted in the lives of the marin people: it should grow, develop, be sincere (gentle), strong, strong and have a protective nature. By means of qualitative research methods and the type of descriptive research, the writer would do a data collection by observation and interview to collect the necessary data so as to assist the writer in developing the writer's research and be an aid in completing this research that is used as a tool to complete the research. The theory of symbolic interaction is the theory of communications used by the writer as the basis for this study so that as the study continues, it will not stray far from the basis of the theory and rumuse. In this writing, the author wants to expound on the symbolic coconut communication media as a symbol or totem of marind society particularly the gebze clan in an effort to preserve the culture.